An Analysis of Grammatical Cohesion Found in Steve Harvey TV Show Conversation: Discourse Analysis Approach - Hakim, Muhammad Arsyad; Ambalegin ambalegin (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
The purpose of this study was to analyze the types of grammatical cohesion contained in the Steve Harvey TV Show. Then, the conversation was analyzed and classified by applying the theory of Halliday and Hasan (1976) to the data source. The method of this research, the researchers used was descriptive qualitative method. The data collection technique of this research, the researchers were using observation. The researchers found the entire total of this study amounted to fifteen data. ten data personal, two conjunctions, and three demonstrative. Researchers hope that with this research, readers can understand and can be used as reference material in making research. And researchers hope that this research can support other studies.